2018
DOI: 10.5056/jnm18037
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-200a Targets Cannabinoid Receptor 1 and Serotonin Transporter to Increase Visceral Hyperalgesia in Diarrhea-predominant Irritable Bowel Syndrome Rats

Abstract: Background/AimsMicroRNAs (miRNAs) were reported to be responsible for intestinal permeability in diarrhea-predominant irritable bowel syndrome (IBS-D) rats in our previous study. However, whether and how miRNAs regulate visceral hypersensitivity in IBS-D remains largely unknown.MethodsWe established the IBS-D rat model and evaluated it using the nociceptive visceral hypersensitivity test, myeloperoxidase activity assay, restraint stress-induced defecation, and electromyographic (EMG) activity. The distal colon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 38 publications
1
31
0
Order By: Relevance
“…Other literatures have reported that in IBS-D patients, miR-199 and miR-29 are respectively involved in visceral pain and intestinal permeability (34, 35). Our previous studies also have proved that miR-144 and miR-200 by binding to speci c target mRNA play vital roles in IBS-D rats (22,23). However, study on lncRNAs and circRNAs in IBS-D is as yet scarce.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other literatures have reported that in IBS-D patients, miR-199 and miR-29 are respectively involved in visceral pain and intestinal permeability (34, 35). Our previous studies also have proved that miR-144 and miR-200 by binding to speci c target mRNA play vital roles in IBS-D rats (22,23). However, study on lncRNAs and circRNAs in IBS-D is as yet scarce.…”
Section: Discussionmentioning
confidence: 99%
“…More and more studies have given insights into the indispensable roles of ncRNAs played in cellular process (19), tumorigenesis (20), in ammatory regulation (21) and so on. Our previous studies also have reported that microRNA-144 and microRNA-200a are involved in intestinal permeability and visceral hyperalgesia separately by binding to speci c target mRNA in IBS-D rats (22,23). However, exploration about ncRNAs for IBS-D is still negligible.…”
Section: Introductionmentioning
confidence: 97%
“…Other literatures have reported that in IBS-D patients, miR-199 and miR-29 are respectively involved in visceral pain and intestinal permeability [ 34 , 35 ]. Our previous studies also have proved that miR-144 and miR-200 by binding to specific target mRNA play vital roles in IBS-D rats [ 22 , 23 ]. However, the study on lncRNAs and circRNAs in IBS-D is as yet scarce.…”
Section: Discussionmentioning
confidence: 99%
“…More and more studies have given insights into the indispensable roles of ncRNAs played in the cellular process [ 19 ], tumorigenesis [ 20 ], inflammatory regulation [ 21 ], and so on. Our previous studies also have reported that microRNA-144 and microRNA-200a are involved in intestinal permeability and visceral hyperalgesia separately by binding to specific target mRNA in IBS-D rats [ 22 , 23 ]. However, exploration about ncRNAs for IBS-D is still negligible.…”
Section: Introductionmentioning
confidence: 99%
“…The abnormal increase of visceral sensitivity may cause gastrointestinal dysfunction, and visceral hypersensitivity is thought to be an important pathophysiological factor . Diarrhea‐predominant IBS (IBS‐D), the largest sub‐category of IBS, can cause visceral pain, changed bowel habits, and bloating under normal biochemistry or anatomy . The treatments of IBS‐D include fiber supplements, probiotics, antidepressants, and a 5‐hydroxytryptophan 3 receptor antagonist, but those treatments are not so effective .…”
Section: Introductionmentioning
confidence: 99%